Reator de leito fluidizado: revisão de literatura e dimensionamento de reator aplicado em contexto industrial no tratamento do glicerol - Barbosa, Mariana (Universidade Federal de São Carlos, 2022)
Industrial activities are among the most impacting anthropic actions, generating various residues that vary according to their chemical, physical and biological compositions, as well as volume and toxicity potential. With the increasingly stringent environmental regulations, the waste must be characterized, quantified, conditioned and treated appropriately before its final disposal. Companies must indemnify or repair the damage caused to the environment and to third parties, arising from any of their activities, increasing the costs with environmental protection, disposal and treatment of waste. However, the residues are not necessarily rejects without any application, many have the potential to be transformed into by-products or raw materials for other production lines, and may generate new revenue for the company. Glycerol is one of the largest waste generated by biodiesel production and, although it has several industrial applications, the large volumes produced make the co-product difficult to dispose of, reducing its value in the market. The implementation of biotechnological alternatives for the transformation of glycerol into co-products of higher added value has become essential, highlighting in this context the use of Pseudomona aeruginosa for the production of rhamnolipids or biosurfactants, which can be used in various sectors in the pharmaceutical, food, oil, among others. In this context, biotechnological strategies can be employed, such as bioreactors, capable of conducting a series of chemical reactions catalyzed by enzymes or microbial, animal or plant living cells, promoting the treatment of waste and generating coproducts resulting from this biodegradation. The Fluidized Bed Bioreactor (FBBR) presents several potentialities compared to other reactors, such as the high conversion efficiency of organic substrates, due to the high concentration of biomass adhered to the support material. In view of the mentioned aspects, this work aimed to describe the main phenomena and characteristics of the fluidized bed reactor, besides identifying the applications of this reactor for the treatment of industrial waste and potential generation of co-products of economic interest, through a literature review, as well as the design of a pilot FBBR reactor for glycerol treatment and biosurfactant production. The dimensioned reactor has 8.85 m of height, 0.268 m of internal diameter and 500 L of capacity, using crushed rubber as support material, its estimated glycerol consumption and biosurfactant production was 42004,8 g and 7200 g per day, respectivelyIt. Was found that FBBR reactor has several potentialities and that there are many applications for the treatment of industrial waste, besides its applicability for biodiesel producing industries, as an alternative to the surplus of glycerol in the market and as a way to add value to the waste.
Fluid bed reactor: literature review and reactor sizing applied in industrial context in glycerol treatment
Keywords: Reator de leito fluidizado; Tratamento; Resíduos industriais; Glicerol; Biossurfactante; Fluidized bed bioreactor; Treatment; Industrial waste; Glycerol; Biosurfactant; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL